The World Crisis, 1911-1914. - Churchill, Winston S. (Winston Churchill World Crisis Collection., 2013)
The causes of the Great War are examined in this first volume of the series that is "essential reading, as fresh and compelling as ever" (Jon Meacham, bestselling author of Franklin and Winston). An absorbing history of the outbreak of World War I from a true insider's point of view, the first volume of Sir Winston Churchill's five-volume The World Crisis is unsurpassed as both a historical and personal account of the earth-shaking events leading up to World War I. Beginning in 1911, when Churchill was First Lord of the Admiralty, this report is based on thousands of his personal letters and memos. Churchill's epic series opens with a chilling description of the Agadir Crisis, and provides an in-depth account of naval clashes in the Dardanelles, one of Churchill's major military failures. It takes readers from the fierce bloodshed of the Gallipoli campaign to the tragic sinking of the Lusitania and the tide-turning battles of Jutland and Verdun'as well as the USA's entry into the combat theatre. Written in powerful prose by a great leader who would also go on to receive a Nobel Prize in Literature, The World Crisis provides a perspective you won't find anywhere else: a dynamic insider's account of events that would shape the outcome of modern history. "Whether as a statesman or an author, Churchill was a giant; and The World Crisis towers over most other books about the Great War." 'David Fromkin, author of A Peace to End All Peace.